Implementasi Pembelajaran STEAM Melalui Permainan Coding Robotik Dalam Melatih Problem-Solving Anak Usia Dini - N. Siti Sopiah; Sima Mulyadi; Aini Loita (Early Childhood Islamic Education, 2023)
The purpose of this study is to describe the implementation of extracurricular STEAM robotic coding in training problem-solving skills for young children at Joy Kids National Plus Tasikmalaya Kindergarten. This type of research uses a descriptive qualitative approach through direct data collection at the research location. Data was obtained through literature study, observation, interviews with teachers, and documentation studies. Data analysis uses descriptive. The research results show that the process of implementing STEAM robotic coding learning includes the stages of child conditioning, apperception and provocation. The type of coding used is unplugged coding as the activity is able to provide stimulus to children in observing, recognizing and understanding the meaning of the commands contained in the circuit including direction and sequence. Through extracurricular robotic coding, STEAM can facilitate early childhood problem-solving skills by demonstrating skills in observing objects (observation), gathering information (collecting), processing information (Analyzing), and communicating information (communicating).